2009
DOI: 10.1002/cctc.200900062
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Carbonylation Reactions of Alkenes and Alkynes

Abstract: Palladium‐catalyzed carbonylation reactions of alkenes and alkynes with different nucleophiles have undergone rapid development ever since the seminal work of Reppe back in the 1930s. Nowadays, a plethora of palladium catalysts and various synthetic protocols are available for the synthesis of valuable carboxylic acids and acrylic acids as well as their derivatives. Herein, we summarize the recent catalyst developments and selected organic applications in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
123
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 402 publications
(123 citation statements)
references
References 261 publications
(146 reference statements)
0
123
0
Order By: Relevance
“…Initially, we selected 1a as a standard substrate to search for potential co-oxidants. The reaction of 1a with [Pd(tfa) 2 Substrates 1i-l bearing alkyl substituents at the alkyne terminus were transformed to the corresponding ketones 2j-l in 71%-92% yield (Table 2, Entries 9-12). Free hydroxyl groups were also tolerated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, we selected 1a as a standard substrate to search for potential co-oxidants. The reaction of 1a with [Pd(tfa) 2 Substrates 1i-l bearing alkyl substituents at the alkyne terminus were transformed to the corresponding ketones 2j-l in 71%-92% yield (Table 2, Entries 9-12). Free hydroxyl groups were also tolerated.…”
Section: Resultsmentioning
confidence: 99%
“…Cascade reactions are important tools for constructing a variety of heterocycles in one step starting from simple compounds [1][2][3][4]. Recently, we reported that the cyclization-carbonylation-cyclization coupling reaction (CCC-coupling reaction) of (o-alkynyl phenyl) (methoxymethyl) sulfides 1 catalyzed by palladium(II)-bisoxazoline (box) complexes afforded bis(benzothiophen-3-yl) methanones 2 in good yield (Scheme 1) [5].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The methoxycarbonylation of ethylene (Scheme 1, R 1 = H and R 2 = CH 3 ) to obtain methyl propionate (MP) is of particular interest, due to the importance of MP as an intermediate in the production of methyl methacrylate (MMA) as a monomer applied to make poly-methylmethacrylate ( p-MMA) 4 -a transparent thermoplastic polymer in high demand with many useful applications such as alternative to glass, medical technologies, implants, etc.…”
Section: Introductionmentioning
confidence: 99%
“…We note that an enhanced signal is also seen at  9.52 for HOTf in these NMR spectra and that neither of these signals are seen in methanol-d 4 itself, or when a single equivalent of CH 3 OH is added to this CD 2 Cl 2 solution as both signals are replaced by an enhanced peak at  7.84 for 6. The formation of this triflic acid product is consistent with the promotion of this reaction with added acid.…”
Section: Detection Of Phhc=c(ph)co(otf)mentioning
confidence: 72%
“…3,4 Consequently, these developments illustrate just how critical early studies on the mechanism of the methoxycarbonylation of alkenes, 2,5 and more generally the palladium catalysed hydroformylation of alkenes 6,7 were for the development of an array of new clean technologies. 3 For a number of years, the parahydrogen (p-H 2 ) 8 induced polarization (PHIP) 9, 10 effect has been used to yield mechanistic insight into a range of catalytic hydrogenation and hydroformlyation reactions besides monitoring the formation of metal hydride based products. 11,12 These studies employ the PHIP effect to increase the 1 H NMR signal strengths of reaction products that contain protons which were originally located in a molecule of p-H 2 to achieve this goal.…”
Section: Introductionmentioning
confidence: 99%